Dynamics of Socio-Economic and Cultural Changes on Agribusiness Institutions in Oil Palm Development Areas in West Sulawesi Province, Indonesia - Abd. Azis; Rusdiaman Rauf; Semuel Pajala (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to examine the role of agribusiness institutions in shaping socio-economic and cultural changes among oil palm smallholders in West Sulawesi, Indonesia, and to assess the involvement of government and private companies in supporting smallholder farmers’ economic improvement within the nucleus–plasma partnership system. Research Method: A qualitative descriptive-analytic approach was applied. Data were collected through in-depth interviews, participatory observation, and document analysis, involving smallholders, managers of agribusiness institutions, private-sector actors, and relevant government agencies. Thematic analysis was conducted through data reduction, presentation, and conclusion drawing, with triangulation across multiple sources to ensure validity. Results and Discussion: The findings reveal that agribusiness institutions have not significantly influenced smallholders’ economic levels. Limited government and private sector participation have restricted access to capital, technology, and market information. Despite this, smallholders’ independent cultivation of oil palm has improved household income and driven cultural transformation, shifting traditional farming practices toward more modern, market-oriented practices. Implications: Strengthening agribusiness institutions through active collaboration between government, private companies, and farmers is essential for sustainable development and equitable benefits. Policy measures should focus on capacity building, facilitating access to finance, technology transfer, and market integration. Further research is recommended to explore effective models of institutional intervention and to assess the long-term socio-economic and cultural impacts of agribusiness support on smallholder communities.